Design of Website for Business Enterprises Using a Website Creation Application - Cahyadi, Arif Try; Miftahudin, Nizar; Suci Islahiyah, Neng; Dewi Yulianti, Fanny; Nubla Hanifati Masturah, Bahirah (Universitas Komputer Indonesia, 2022)
The purpose of this research is to utilize information technology in the era of the Covid-19 pandemic in designing websites that are useful in promoting types of businesses for the Micro, Small & Medium Enterprises sector. The method used in this research is descriptive qualitative which focuses on the design process which begins with organizing the concept to the website of the work produced. The result of this research is the design of the Micro, Small & Medium Enterprises website using the wix.com application as a model in designing the website, because the researcher wants to know the process of making a website using the application without losing the design principles and the user interface. So in this study, we can find out the website design process using the wix.com application which is considered easier to use, easy to access, and practical.